Optimalisasi Peran Perpustakaan Sekolah Guna Meningkatkan Budaya Minat Baca Peserta Didik SMA Xaverius 5 Belitang - Andreas Waluyo; Andi Khaerun Nisa (UPT Perpustakaan UIN Alauddin Makassar, 2023)
Abstract A low reading culture can describe a country from its identity. This is all illustrated by the lack of visitors in the library, especially the school library. In this study the aim was to analyze the optimization of the role of the Xaverius 5 Belitang Senior High School library in fostering students' interest in reading. The method used is qualitative with narrative type and observation and interview techniques. The results of the research show that the Xaverius 5 Belitang High School Library is slowly starting to carry out various activities in order to increase students' interest in reading through optimizing the role of the library, namely: Mobile Reading Program, One Page Reading, and Book Reviews or reviewing book readings. Apart from that, the library also created a Library Reading Terrace, namely providing bookshelves on the library terrace. Therefore, libraries experience several obstacles in optimizing the role of the library, namely limited funds to purchase reading books, limited library space conditions, and unattractive library room design. Keywords: Reading Interest; Service Optimization; School Library